DNA Hypomethylation, Ambient Particulate Matter, and Increased Blood Pressure: Findings From Controlled Human Exposure Experiments. Issue 3 (19th June 2013) - Bellavia, Andrea; Urch, Bruce; Speck, Mary; Brook, Robert D.; Scott, Jeremy A.; Albetti, Benedetta; Behbod, Behrooz; North, Michelle; Valeri, Linda; Bertazzi, Pier Alberto; Silverman, Frances; Gold, Diane; et al.
Abstract : Background: Short‐term exposures to fine (<2.5 μm aerodynamic diameter) ambient particulate‐matter (PM) have been related with increased blood pressure (BP) in controlled‐human exposure and community‐based studies. However, whether coarse (2.5 to 10 μm) PM exposure increases BP is uncertain. Recent observational studies have linked PM exposures with blood DNA hypomethylation, an epigenetic alteration that activates inflammatory and vascular responses. No experimental evidence is available to confirm those observational data and demonstrate the relations between PM, hypomethylation, and BP. Methods and Results: We conducted a cross‐over trial of controlled‐human exposure to concentrated ambient particles (CAPs). Fifteen healthy adult participants were exposed for 130 minutes to fine CAPs, coarse CAPs, or HEPA‐filtered medical air (control) in randomized order with ≥2‐week washout. Repetitive‐element ( Alu, long interspersed nuclear element‐1 [LINE‐1]) and candidate‐gene ( TLR4, IL‐12, IL‐6, iNOS ) blood methylation, systolic and diastolic BP were measured pre‐ and postexposure. After adjustment for multiple comparisons, fine CAPs exposure lowered Alu methylation (β‐standardized=−0.74, adjusted‐ P =0.03); coarse CAPs exposure lowered TLR4 methylation (β‐standardized=−0.27, adjusted‐ P =0.04). Both fine and coarse CAPs determined significantly increased systolic BP (β=2.53 mm Hg, P =0.001; β=1.56 mm Hg, P =0.03, respectively) and nonsignificantly increased diastolic BP (β=0.98 mm Hg, P =0.12; β=0.82 mm Hg, P =0.11, respectively). Decreased Alu and TLR4 methylation was associated with higher postexposure DBP (β‐standardized=0.41, P =0.04; and β‐standardized=0.84, P =0.02; respectively). Decreased TLR4 methylation was associated with higher postexposure SBP (β‐standardized=1.45, P =0.01). Conclusions: Our findings provide novel evidence of effects of coarse PM on BP and confirm effects of fine PM. Our results provide the first experimental evidence of PM‐induced DNA hypomethylation and its correlation to BP.